Assessment of Trade Performance and Growth Potential of Lemongrass Oil Export in India - Choudhri, Harendra Pratap Singh; Verma, Deepak Kumar; Sharma, Ram Suresh; Kumar, Sanjay (International Journal of Economic Plants, 2025)
The present study aimed to analyze the growth and potential of lemongrass oil exports over twenty years from 2003–04 to 2022–23 across India. The growth and potential of lemongrass oil were estimated based on secondary data of EXIM in quantity and value obtained from the Department of Commerce, Ministry of Commerce and Industry, Government of India for twenty years using statistical tools like the growth model and Cuddy-Della Valle index. Among the top ten countries or destinations of India’s lemongrass oil export were the maximum shares (quantity and value) of importing countries i.e. USA followed by China PRP and Germany. The compound growth rate of the last twenty years both in quantity and value of lemongrass oil were analyzed 16.08 and 25.20% and the variation was 72.73% in quantity and 102.03% in value respectively, indicating the good potential and sustainable supply of Indian lemongrass oil in the world market. The continuously increasing domestic and global demand for lemongrass oil has good opportunities for earning foreign exchange and promotion in the Indian Aroma industry. The area under lemongrass cultivation provided employment opportunities for rural people especially agricultural workers and resource-poor people. It also offered a sustainable source of round-the-year income, better options for crop diversification, and utilization of marginal land.